Facilities and Infrastructure Management in Improving the Quality of Student Learning - Handayani, Rejeki; Hidayat, Hidayat (Journal of Innovation and Research in Primary Education, 2025)
Effective facilities and infrastructure management represents a critical determinant of educational quality in Islamic primary education institutions, yet limited research examines how management functions operate within madrasah contexts. This study investigates the implementation of Terry's management theory—encompassing planning, organizing, implementing, and supervising functions—in facilities and infrastructure management at Madrasah Ibtidaiyah to enhance learning quality. A qualitative case study approach was employed at Madrasah Ibtidaiyah Cisarua Girang, Sukabumi City, utilizing purposive sampling to select key stakeholders including the principal, infrastructure management team, teachers, and administrative staff. Data collection involved in-depth interviews, direct observation, and document analysis of institutional records. Data validity was ensured through source and methodological triangulation, while analysis followed Miles, Huberman, and Saldana's interactive model with systematic coding according to Terry's four management functions. The madrasah implemented structured facilities management through RKAS planning documents, though only 65% of planned improvements achieved completion due to budget constraints and limited stakeholder participation (23% teacher involvement). Organizational challenges included absence of standardized procedures for 67% of infrastructure tasks and dual-responsibility constraints for personnel. Implementation strategies demonstrated creativity through dual-session learning systems and 82% community participation in infrastructure improvements. Supervision utilized regular monitoring with 45% recommendation implementation rates, though manual documentation systems limited efficiency. Findings reveal that effective infrastructure management in resource-constrained Islamic education contexts requires adaptive strategies beyond traditional administrative approaches. The madrasah's community-based solutions and innovative space utilization demonstrate institutional resilience that transcends physical limitations. However, systematic stakeholder engagement, standardized organizational procedures, and digital supervision systems represent critical areas for enhancement to optimize learning quality outcomes.